Kegiatan Preservasi Bahan Pustaka di Perpustakaan IKOPIN University - Salsa Amalia Putri; Ninis Agustini D; Ute Lies Siti Khadijah; Saleha Rodiah; Samson CMS; Evi Nursanti Rukmana; Lutfi Khoerunnisa (UIN Maulana Malik Ibrahim Malang, 2023)
Preservation is a series of activities that include maintenance, care, preservation, and prevention of collection materials. The essence of the existence of preservation activities is to ensure that the information content is in a good condition to be used or accessed in an unspecified time. The purpose of this study is to determine the preservation activities carried out on collection materials at the IKOPIN University Library. The research method used is descriptive qualitative method with a case study approach. The data collection techniques used in this research are interviews, observation, and literature study. Interviews were conducted with 2 resource persons, namely the Head of the IKOPIN University Library and the user. Interviews and observations were carried out directly. The data analysis carried out is the data analysis model by Miles and Huberman which consists of 3 stages: data reduction, data presentation, and drawing conclusions and verification. The results of the study show that the IKOPIN Library has carried out a series of preservation activities. The activities carried out were packaging books with plastic covers, bookbinding, cleaning book collections, transfer of collection materials, environmental control, temperature regulation, lighting regulation, hygiene monitoring, and awareness training on preservation activities. In the research conducted, it was also found that the factors causing damage to collections in the IKOPIN library were the main factors, namely book characteristics and human factors. The conclusion from the research is that the IKOPIN library has an awareness of the importance of preservation activities, therefore the IKOPIN library has carried out preservation activities both actively, passively, and preventively. The preservation implementation found 2 obstacles, namely in the field of HR (Human Resources) and the field of funding.